Association between BAFF gene polymorphism and systemic lupus erythematosus: a meta-analysis - Qing Wu; Qin Zhang; Dong-Qing Ye (Egyptian Journal of Medical Human Genetics)
Abstract Objective To inquire into the association from BAFF gene promoter -871C > T single nucleotide polymorphisms (SNP) to the etiopathogenesis of systemic lupus erythematosus (SLE) and to further discuss the interracial differences through ethnostratified methods. Methods All researches exploring the link of BAFF gene promoter-871C > T single nucleotide polymorphisms (SNPs) with SLE before February 2023 were retrospectively selected, and the allele frequency was calculated by allele counting. Results The study amalgamates data from five independent researches, encompassing a total of 514 cases and 605 controls. A statistically significant correlation is observed in the recessive model (OR = 0.64, 95% CI: 0.50–0.82, P < 0.001), as well as in the allelic model (OR = 0.63, 95% CI: 0.42–0.95, P = 0.026). However, no statistically significant associations are found in the Dominant model (OR = 0.84, 95% CI: 0.59–1.21, P = 0.352), CC vs. TT (OR = 0.70, 95% CI: 0.47–1.03, P = 0.073), and CT vs. TT (OR = 1.04, 95% CI: 0.71–1.53, P = 0.852). Additionally, both the funnel plot and Begg’s test for publication bias indicate no discernible asymmetry, with all P values exceeding 0.05. This suggests an absence of publication bias in the study. Conclusion The correlation between BAFF gene promoter polymorphism-871C > T allele frequency and mutant genotype T and SLE risk was demonstrated, and a stronger correlation was found in the population subgroup analysis compared with non-Asians.